EXPLORING THE IMPACT OF CRITICAL DISCOURSE ANALYSIS (CDA) ON ENHANCING 21ST CENTURY TEACHERS’ CRITICAL READING ABILITIES - Sari, Cut Purnama; Santoso, Anang; Roekhan, Roekhan; Susanto, Gatut (English Review: Journal of English Education, 2024)
This research aims to investigate the relationship between critical reading abilities and critical discourse analysis (CDA) competencies among future 21st century educators, emphasizing the critical necessity for these educators to possess such skills in today's demanding educational landscape. A sample of 70 prospective teachers was analyzed to determine the interconnection between their abilities in critical reading abilities and CDA, with an exploration into how one skill may influence the other. Additionally, the study examines the role of cognitive style—specifically, field-independent and field-dependent thinking—as a moderating factor in this relationship. Findings indicate a significant positive impact of CDA capabilities on critical reading abilities, suggesting that proficiency in analyzing discourse critically enhances one's ability to read with a critical eye. Furthermore, the study reveals no significant difference in CDA and critical reading abilities between participants categorized as field-independent thinkers versus those identified as field-dependent thinkers. These outcomes highlight the need for further research to explore additional factors that may affect the development of critical reading and discourse analysis skills. The study concludes with a call for educational strategies that integrate both critical reading and CDA competencies, considering the varied cognitive styles of learners.